Hubungan Pengetahuan K3 dengan Hasil Praktikum Mahasiswa di Workshop Konstruksi Teknik Sipil FT UNP - Nurhasan Syah; Jonni Mardizal; Fitra Rifwan; Zulkifli Gusti Arianto (Universitas Negeri Padang, 2020)
This research aims to (1) know how much knowledge of Occupational Health and Safety (OHS) Students of the Department of Civil Engineering Faculty of Engineering of Padang State University class of 2019, (2) Know how high the results of OHS practices Students of the Department of Civil Engineering Faculty of Engineering Of Padang State University class of 2019, (3) know the relationship of OHS knowledge with the results of student practice in the Construction Workshop of Civil Engineering Faculty of Engineering Padang State University. This research is a correlational descriptive study. Instrument validation is tested with expert judgement and score percentage to assess data and analysis of question items. The results showed that (1) ohs knowledge of students of the Department of Civil Engineering Faculty of Engineering Padang State University class of 2019 fall into the high category. The results of the analysis of the data that has been done, obtained a percentage score of 80.94%. This shows that Students of the Department of Civil Engineering Faculty of Engineering Padang State University class of 2019 have a high basic knowledge of OHS, (2) The results of practicum students of the Department of Civil Engineering Faculty of Engineering Padang State University class of 2019 fall into the high category. The results of the data analysis that has been done, obtained a high percentage score of 81.25%, (3) there is a significant positive relationship between ohs knowledge and the results of student practicum at the Civil Engineering Workshop of the Faculty of Engineering of Padang State University. This is indicated by a correlation coefficient of pearson product moment of 0.483 and fall into the moderate category.